eDisc: Sistem Layanan Antrian Kantor Camat Palongbangkeng Utara Kabupaten Takalar - Ifani, Aulyah Zakilah; Agunawan, Agunawan; Darius, Andi Devina Yaritsha; Juharman, Muh.; Ferlita, Andi Iza (PT. Lontara Digitech Indonesia, 2024)
The creation of widespread technological innovation makes it easier for people to live their lives. The sub-district office has a task that is not far from serving the community, taking care of various administrations to take care of things. However, the low quality of employee service has hampered sub-district office services. With this, the researchers aim to design an online-based queuing system that will make it easier for employees and the public to take care of things at the sub-district office. The population used in this study were 23 students in Makassar. The collection technique is in the form of literature study and distributing online questionnaires. The test uses Black Box Testing to test the usability of its features. The results of the study show that e-District (eDisc) has proven good and can be used as an online-based queuing system at the sub-district office.